2021
DOI: 10.22159/ajpcr.2021.v14i11.42757
|View full text |Cite
|
Sign up to set email alerts
|

A Pragmatic Approach to Treat Lung Cancer Through Loading Theaflavin -3,3’-Digallate and Epigallocatechin Gallate in Spanlastic

Abstract: Lung cancer has the highest mortality rate as compared to other cancers. The anti-proliferative and antioxidant potential of epigallocatechin gallate (EGCG) and Theaflavin -3,3’-digallate (TF3) can play a major role in treatment if delivered efficiently. To improve the chemical stability and medicinal potential of EGCG and TF3 in the respiratory tract, a spanlastic is developed which is composed of Tween-80, Span-60, and cholesterol which encapsulate EGCG and TF3 inside its vesicular structure and deliver it s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 68 publications
0
7
0
Order By: Relevance
“…Nanoparticles such as transferosomes are new generation novel drug delivery system which is quite stable at 7.4 pH and its efficacy and drug entrapment potential are better than other conventional nanoparticle systems. These natural products loaded in nanoparticles then loaded in pMDI canisters such as fluorocarbon polymerization (FCP) plasma-coated canisters with a better propellant such as HFA-134a and delivered with the help of spacers can cure lungs cancer economically, efficiently with minimal side effects and it also ensures that the cancer will not reoccur [48].…”
Section: Delivery Methodsmentioning
confidence: 99%
“…Nanoparticles such as transferosomes are new generation novel drug delivery system which is quite stable at 7.4 pH and its efficacy and drug entrapment potential are better than other conventional nanoparticle systems. These natural products loaded in nanoparticles then loaded in pMDI canisters such as fluorocarbon polymerization (FCP) plasma-coated canisters with a better propellant such as HFA-134a and delivered with the help of spacers can cure lungs cancer economically, efficiently with minimal side effects and it also ensures that the cancer will not reoccur [48].…”
Section: Delivery Methodsmentioning
confidence: 99%
“…Prothrombin time is an intermediate end objective, whereas renal failure and arrhythmia are toxic end points. The prevention of stroke, pulmonary embolism, and seizure episodes are therapeutic end points [38]. A feasible intermediate end goal may be employed in the absence of readily visible hazardous or therapeutic end points.…”
Section: Characteristic Of Therapeutic Drugs Applicable For Monitoringmentioning
confidence: 99%
“…Comparably, it has been observed that a combination of beta-carotene, lutein, and lycopene carotenoids protects against erythema. Studies on the photoprotective properties of vitamins C and E have shown that they are useful for maintaining skin health [39]. Hydrophilic in nature, vitamin C is often consumed in high quantities through a variety of food products, with the aim of preventing the development of nitrous oxide metabolites that cause cancer.…”
Section: Carotenoidsmentioning
confidence: 99%